Medical and Productivity Costs of Rheumatoid Arthritis in The Czech Republic: Cost-of-Illness Study Based on Disease Severity - Klimeš, Jiří; Vocelka, Milan; Šedová, Liliana; Doležal, Tomáš; Mlčoch, Tomáš; Petříková, Alena; Vlček, Jiří (Value in health regional issues, 2014)
OBJECTIVE: International pharmacoeconomic studies suggest that functional impairment can be a significant predictor for the evaluation of direct and productivity costs for rheumatoid arthritis (RA). We calculated the direct and productivity costs for five Health Assessment Questionnaire (HAQ) groups of patients (HAQ scores <0.6, 0.6 ≥ 1.1, 1.1 ≥ 1.6, 1.6 ≥ 2.1, and ≥2.1) in the Czech Republic. METHODS: This was a retrospective cross-sectional study. We included 261 patients with RA, aged 18 to 84 years. We applied a bottom-up method by retrospectively reviewing individual patient medical records. Patients' demographic characteristics, patient-reported outcome, and clinical parameters were gathered at the time of data collection. For the calculation of productivity costs, we used the friction cost approach, based on patient absenteeism with a friction period of 130 workdays, with average monthly income used as the denominator. Costs were expressed as a mean value per patient with RA in each HAQ group. RESULTS: Mean patient age was 56.4 years. average time from diagnosis was 14.5 years, the mean HAQ score was 1.15, and the Disease Activity Score in 28 joints was 3.45. A total of 47.5% patients were treated with biologics. Mean annual direct medical costs for each HAQ group were €5315, €7357, €7697, €7716, and €8968, respectively. The mean annual indirect costs associated with productivity loss were €1414, €1459, €1610, €1876, and €2307, respectively. CONCLUSIONS: Direct costs and productivity costs for patients with RA are closely related to the value of the HAQ score. The annual mean total (direct plus productivity) costs per patient 1) treated with biologics, 2) without biologic treatment, and 3) from the overall cohort were €14,763, €3,559, and €8,882, respectively.
Keywords: rheumatoid arthritis; quality of life; health economics; cost-of-illness